Applied evolutionary psychology - Roberts, S. Craig (Oxford : Oxford University Press, 2012)
This title considers how basic evolutionary thinking is being applied to a wide range of special social, economic, and technical problems. It draws together a collection of renowned academics from a very disparate set of fields, whose common interest lies in using evolutionary thinking to inform their research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Evolutionary psychology; Psychology, Applied